Peran Gut Microbiome pada Attention Deficit Hyperactivity Disorder (ADHD) - Setiani, Ariana; Maharatih, Gusti Ayu (Majalah Kedokteran Indonesia, 2025)
Attention deficit hyperactivity disorder (ADHD) is a behavioral disorder, associated with neurodevelopmental disorders in the form of persistent patterns of inattention or hyperactivity and impulsivity that interfere with childhood functioning and development. The prevalence of ADHD is estimated at 3.4% in children and adolescents worldwide.1 In 60-80% of cases, ADHD symptoms persist into adulthood.2